2017
DOI: 10.2298/pif1704145v
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and distribution of leek yellow stripe virus in allium crops in Serbia

Abstract: Leek yellow stripe virus (LYSV) is one of the most frequent and important viruses in leek and garlic crops worldwide. In Serbia this virus is found both in leek and garlic, and often at high percentages. During two consecutive years, 2012 and 2013, a total 92 samples were collected from 11 inspected leek-, garlic-and onion-growing locations and they were analyzed for the presence of LYSV using DAS-ELISA. LYSV was detected in 31.5% of the tested samples. In 2012, the presence of LYSV was only detected in leek p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
4
0
2
Order By: Relevance
“…Therefore, the low LYSV infection rate could most likely be attributed to the absence of aphid vectors on fields that limit the spread of LYSV. Low LYSV infection rates on onions were also reported on surveys in other regions of Turkey and other countries (Dovas and Vovlas 2003, Fidan 2010, Sevik and Akcura 2013, Vučurović et al 2017). However, infection rate of 60.1% was observed in Tehran region of Iran (Shahraeen et al 2008).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the low LYSV infection rate could most likely be attributed to the absence of aphid vectors on fields that limit the spread of LYSV. Low LYSV infection rates on onions were also reported on surveys in other regions of Turkey and other countries (Dovas and Vovlas 2003, Fidan 2010, Sevik and Akcura 2013, Vučurović et al 2017). However, infection rate of 60.1% was observed in Tehran region of Iran (Shahraeen et al 2008).…”
Section: Discussionsupporting
confidence: 58%
“…LYSV infects garlic and leek and is detected in garlicgrowing areas worldwide. Although onions generally are not considered to be natural hosts for LYSV (Katis et al, 2012;Vučurović et al, 2017), onion damage due to LYSV infection has also been reported in some regions (Santosa and Ertunç, 2020;Sharhraeen et al, 2008). LYSV detected in garlic-growing areas in Japan can be classified into two types, northern type (LYSV-N) and southern type (LYSV-S), based on a characteristic deletion of 200-300 bases in the P1 gene (Takaki et al, 2005;Yoshida et al, 2012).…”
mentioning
confidence: 99%
“…Leek yellow stripe virus (LYSV) is one of the potyviruses infecting garlic in many countries including southern/eastern EU states (Vončina et al, 2016;Vučurović et al, 2017), but was never reported from Ukraine. Using doubleantibody sandwich enzyme-linked immunosorbent assay with virus-specific antibodies, LYSV was detected in 28% of samples from 3/4 screened regions of Ukraine, similarly to previously described OYDV in Ukraine (Snihur et al, 2019).…”
Section: Discussionmentioning
confidence: 99%